High-entropy ceramic wave-absorbing material and design method and preparation method thereof
By designing the BaBO3 perovskite structure and the multi-level system synergistic polarization mechanism, high-entropy ceramic microwave absorbing materials were prepared, solving the stability and efficiency problems of electromagnetic wave absorbing materials under high temperature conditions, and achieving high-strength and high-stability electromagnetic wave absorption effects.
Patent Information
- Application Number
- CN202511247675.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-03
- Publication Date
- 2025-12-19
AI Technical Summary
Existing electromagnetic wave absorbing materials have insufficient absorption efficiency and high reflectivity under high temperature and harsh environments, making it difficult to achieve wideband coverage, and they also have poor stability.
Using BaBO3 perovskite as a structural model, high-entropy ceramic microwave absorbing materials were prepared by combining five ions in equal proportions and designing a multi-level system synergistic polarization mechanism, doping with rare earth, transition metals and high bond energy ions, and combining multi-particle size pressing technology.
It maintains dielectric stability within a temperature range of -120 to 800℃, achieving stable electromagnetic wave absorption at high temperatures. It features high strength, high stability, and high density, making it suitable for high-temperature environments.
Smart Images

Figure CN121168022A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of wave-absorbing materials, and particularly relates to a high-entropy ceramic wave-absorbing material and a design method and a preparation method thereof. BACKGROUND
[0002] With the rapid development of wireless communication, radar systems, and electronic warfare, electromagnetic interference and electromagnetic radiation have brought increasingly serious impacts on electronic devices and human health, and therefore, it has become a common focus of the scientific research and industrial communities to develop electromagnetic wave-absorbing materials with high efficiency, good mechanical properties, corrosion resistance, high-temperature resistance, and controllable performance.
[0003] At present, the existing electromagnetic wave-absorbing materials mainly include metal-based materials, magnetic materials, porous ceramics, and high-dielectric-loss composite materials. These materials realize partial absorption of electromagnetic energy by using electric conductivity, magnetic loss, or multiple scattering mechanisms. For example, CN119609126A discloses a surface mechanical alloying coated zinc carbonyl iron powder absorber and a preparation method thereof. A uniform and dense zinc coating layer is generated on the surface of the carbonyl iron powder by using a ball milling mechanical alloying process, serving as an absorber of electromagnetic wave-absorbing materials. By precisely controlling the thickness and uniformity of the coating layer, the material improves the electromagnetic wave absorption efficiency while overcoming the problem of insufficient seawater corrosion resistance. Although the material improves the problem of easy corrosion of the metal coating, it still has deficiencies in terms of thermal stability and applicability. Compared with metal powder materials, thin film, foam, and ceramic-based wave-absorbing materials have better corrosion resistance and mechanical strength, which are more suitable for complex environments such as aerospace and radar. CN117263165A provides a melamine foam (MF) as a base skeleton, which is impregnated with carboxymethyl cellulose (CMC) and carbonized to prepare a carbon foam material. The high-porosity MF skeleton structure is connected to form an interconnected layered network structure, which improves the loss of electromagnetic waves and has high impedance matching characteristics, achieving full-frequency effective absorption. The composite carbon foam material also exhibits advantages in terms of wave-absorbing performance and light weight, but its mechanical strength cannot meet the development needs of the aerospace field, and its high-temperature resistance needs to be further improved. CN118993733A provides a magnetic high-entropy perovskite wave-absorbing material and a preparation method thereof. Lanthanum salt, barium salt, strontium salt, calcium salt, sodium salt, and manganese salt are mixed with a complexing agent and a dispersing agent, and a precursor is prepared by using a sol-gel method. The dried precursor is placed in a muffle furnace for calcination to obtain a magnetic high-entropy perovskite wave-absorbing material. The material retains the advantages of high ceramic strength, high heat resistance, high stability, and corrosion resistance, and can meet the application needs of some complex fields. However, although this new type of high-entropy ceramic can enhance the absorption of electromagnetic energy through multiple scattering and polarization mechanisms, its entropy value is low, the induced polarization effect is limited, and the electromagnetic wave absorption performance needs to be further improved. At the same time, the phase structure stability of the material is poor, and the structure holes are difficult to control, making it difficult to realize accurate performance regulation and stable application in high-temperature environments. Summary of the Invention
[0004] To address the technical problems of insufficient absorption efficiency, high reflectivity, difficulty in achieving wide bandwidth coverage, and poor absorption performance stability, especially in high-temperature and harsh environments, existing electromagnetic wave absorbing materials are designed to provide a high-entropy ceramic absorbing material, its design method, and its preparation method. This high-entropy ceramic absorbing material features high strength, high stability, high density, and high temperature resistance, providing a novel approach for the design of high-temperature ceramic-based absorbing materials.
[0005] To achieve the above-mentioned technical objectives, the present invention adopts the following technical solution:
[0006] A design method for a high-entropy ceramic microwave absorbing material includes the following steps:
[0007] (1) Determine BaBO3 perovskite as the structural model and combine the five ions at the B site in BaBO3 perovskite in equal proportions;
[0008] (2) Based on the synergistic polarization of the multi-level system, three ion-doped systems were identified, one of which is a rare-earth ion-doped system, including Yb 3+ Ho 3+ Er 3+ Eu 3+ One type is the transition metal ion doped system, including V 5+ Mn 3+ Fe 2+ Cr 3+ One of them; the third is a high bond energy ion doping system, including Ta 5+ Hf 4+ Zr 4+ Mo 6+ One of them;
[0009] (3) The five ions at the B site are denoted as V1, V2, V3, V4, and V5, respectively, satisfying +2≤V1≤+6; +2≤V2≤+6; +2≤V3≤+6; +2≤V4≤+6; +2≤V5≤+6; V1+V2+V3+V4+V5=+20; and the five ions at the B site must include the three ion doping systems in step (2);
[0010] (4) Establish the mapping relationship between the tolerance factor theory and the structural stability of BaBO3 perovskite, and the formula is as follows:
[0011]
[0012] Among them, R A R B Ba 2+ The average ionic radius of the five ions at the B site, RO Representing O 2- The ionic radius;
[0013] (5) Based on the mapping relationship in step (4), calculate the tolerance factor of the element combination that meets the conditions in step (3), and select the element combination with a t interval of 1-1.05, which is determined as the high-entropy ceramic required for design.
[0014] This invention uses BaBO3 perovskite as a structural model and designs a multi-level system synergistic polarization enhancement mechanism. By using three different types of doping systems—rare earth elements (relatively small ionic radii, small local lattice distortion, easy to undergo low-temperature structural phase transitions or generate small phase transition temperature shifts), transition metal elements (easy to undergo lattice distortion, electronic interactions and magnetic coupling, phase transitions only occur in the mid-temperature region), and high bond energy metal elements (larger ionic radii, easy to improve lattice stability and phase transition activation energy, resulting in the need for high excitation energy for phase transitions)—a B-site doped high-entropy ceramic is designed. This maintains dielectric stability in the temperature range of -120 to 800℃, overcomes the problem of high-temperature dielectric collapse, and achieves stable electromagnetic wave absorption at high temperatures.
[0015] This invention also provides a method for preparing the above-mentioned high-entropy ceramic microwave absorbing material, comprising the following steps:
[0016] (1) BaCO3 was mixed with various metal oxide powders and ball-milled, and then sintered at 900-1100℃ to obtain precursor powder;
[0017] (2) Mix the precursor powder and PVA thoroughly, pass them through several sieves with increasing mesh sizes, and then mix equal masses of powders with different particle size distributions and pour them into a mold for cold pressing to obtain a green body.
[0018] (3) The green body is sintered at 1200-1400℃ to obtain high-entropy ceramic microwave absorbing material.
[0019] Further, in step (1), the molar ratio of Ba in BaCO3 to the total amount of metals in each metal oxide is 1:1; the molar ratio of each metal in the metal oxide is 1:1:1:1:1.
[0020] Further, in step (2), the mass ratio of the precursor powder to PVA is 1:1 to 1.5.
[0021] Further, in step (2), the mesh sizes of the sieves are 60 mesh, 80 mesh and 100 mesh respectively, wherein the particle size distribution of -60 mesh to +80 mesh is denoted as powder A, the particle size distribution of -80 mesh to +100 mesh is denoted as powder B, and the particle size distribution of 100 mesh is denoted as powder C; equal masses of powder A, powder B and powder C are mixed evenly.
[0022] Further, in step (2), the mesh sizes of the sieves are 80 mesh, 100 mesh and 120 mesh respectively, wherein the particle size distribution of -80 mesh to +100 mesh is denoted as powder A, the particle size distribution of -100 mesh to +120 mesh is denoted as powder B, and the particle size distribution of 120 mesh is denoted as powder C; equal masses of powder A, powder B and powder C are mixed evenly.
[0023] It should be noted that, according to the definition of particle mesh, for example, -80 mesh to +100 mesh means that these particles can pass through an 80-mesh screen but not a 100-mesh screen. When screening particles of this mesh size, the larger mesh size (100) should be placed under the smaller mesh size (80) screen. The particles remaining in the larger mesh size (100) screen are those of -80 mesh to +100 mesh, and so on. 120 mesh means that these particles can pass through a 120-mesh screen.
[0024] Furthermore, in step (2), the pressure of the cold pressing is 8-15 MPa, and the time is 30-90 s.
[0025] Further, in step (3), the heating procedure of the sintering process is as follows: first, slowly heat to 550°C at a rate of 1°C / min, and then heat to the target sintering temperature of 1200-1400°C at a rate of 5°C / min.
[0026] The present invention also provides a high-entropy ceramic microwave absorbing material prepared by the above preparation method.
[0027] The beneficial effects of this invention are:
[0028] (1) This invention uses BaBO3 perovskite as a structural model and designs a multi-level system synergistic polarization enhancement mechanism. By using three different types of doping systems, namely rare earth elements (with relatively small ionic radii, small local lattice distortion, easy to undergo low-temperature structural phase transition or generate small phase transition temperature shift), transition metal elements (easy to undergo lattice distortion, electronic interaction and magnetic coupling, phase transition only occurs in the mid-temperature region), and high bond energy metal elements (with larger ionic radii, easy to improve lattice stability and phase transition activation energy, resulting in the need for high excitation energy to undergo phase transition), B-site doped high-entropy ceramics are designed to maintain dielectric stability in the temperature range of -120 to 800℃, overcome the problem of high-temperature dielectric collapse, and achieve stable electromagnetic wave absorption at high temperatures.
[0029] (2) This invention combines the design of a multi-level system synergistic polarization enhancement mechanism with multi-particle size pressing preparation technology, so that the high-entropy ceramic microwave absorbing material has the characteristics of high strength, high stability, high density and high temperature resistance, providing technical support for the design and preparation of durable and reliable high-temperature electromagnetic wave absorbing materials. Attached Figure Description
[0030] Figure 1The high-entropy ceramic Ba(Zn) of Example 1 0.2 Yb 0.2 Ta 0.2 Nb 0.2 V 0.2 The structure diagram and absorption performance diagram of O3 are shown, where (a) is a schematic diagram of atomic configuration; (b) is a total density of states structure diagram; (c) is a 3D reflection loss diagram; and (d) is a 2D reflection loss curve.
[0031] Figure 2 The high-entropy ceramic Ba(Cu) of Example 2 0.2 Yb 0.2 Ta 0.2 Nb 0.2 V 0.2 The structure diagram and absorption performance diagram of O3 are shown, where (a) is a schematic diagram of atomic configuration; (b) is a total density of states structure diagram; (c) is a 3D reflection loss diagram; and (d) is a 2D reflection loss curve.
[0032] Figure 3 The high-entropy ceramic Ba(Cu) of Example 3 0.2 Yb 0.2 Ta 0.2 Nb 0.2 V 0.2 TEM image and absorption performance diagram of O3, where (a) is the TEM image and elemental mapping diagram; (b) is the 3D reflection loss diagram; and (c) is the 2D reflection loss curve.
[0033] Figure 4 The image shows the 3D reflection loss diagram of the sample prepared in Comparative Example 2.
[0034] Figure 5 The image shows the 3D reflection loss diagram of the sample prepared in Comparative Example 3.
[0035] Figure 6 The image shows the 3D reflection loss diagram of the sample prepared in Comparative Example 4. Detailed Implementation
[0036] To make the present invention easier to understand, specific embodiments are described below to further illustrate the invention. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0037] Example 1
[0038] High-entropy ceramics Ba(Zn) 0.2 Yb 0.2 Ta0.2 Nb 0.2 V 0.2 O3, where V Zn =+2,V Yb =+3,V Ta =+5,V Nb =+5,V V =+5.
[0039] 1. Satisfies +2≤V Zn ≤+6; +2≤V Yb ≤+6; +2≤V Ta ≤+6; +2≤V Nb ≤+6; +2≤V V ≤+6; V Zn +V Yb +V Ta +V Nb +V V =+20; and includes Yb in rare earth ion doped systems. 3+ V in transition metal ion doped systems 5+ Ta in high bond energy ion doped systems 5+ .
[0040] 2. The calculation yields t = 1.02.
[0041] Its preparation process is as follows:
[0042] Step 1: Mix BaCO3, ZnO, Yb2O3, Nb2O5, Ta2O5 and V2O5 powders according to the molar ratio of each metal ion of 10:2:2:2:2:2;
[0043] Step 2: Add an appropriate amount of anhydrous ethanol to the mixed powder, and then ball mill at 300 r / min for 24 h. After the process, transfer the mixture to an oven and dry it at a constant temperature of 60℃.
[0044] Step 3: After grinding the dried powder, sinter it at 1000℃ for 10 hours to prepare precursor powder;
[0045] Step 4: Take an appropriate amount of precursor powder, add PVA to it, with a mass ratio of 1:1.2, stir evenly and grind, then pass through an 80-mesh sieve, a 100-mesh sieve and a 120-mesh sieve in sequence. The particle size distribution of -80 mesh to +100 mesh is recorded as powder A, the particle size distribution of -100 mesh to +120 mesh is recorded as powder B, and the particle size distribution of 120 mesh is recorded as powder C. Then mix equal masses of powder A, powder B and powder C evenly and pour into a mold with a diameter of 50 mm for cold pressing at a pressure of 10 MPa for 1 min.
[0046] Step 5: Transfer the pressed powder green body to a muffle furnace for sintering. First, slowly heat it to 550℃ at a rate of 1℃ per minute, and then increase the temperature to the target sintering temperature of 1300℃ at a rate of 5℃ per minute to obtain high-entropy ceramic Ba(Zn) 0.2 Yb 0.2 Ta 0.2 Nb 0.2 V 0.2 )O3.
[0047] like Figure 1 As shown, Ba(Zn 0.2 Yb 0.2 Ta 0.2 Nb 0.2 V 0.2 O3 exhibits a significant lattice contraction phenomenon, with the lattice constant changing from the initial... Adjusted to Effectively suppressed multiphase separation (a); Ba(Zn) 0.2 Yb 0.2 Ta 0.2 Nb 0.2 V 0.2 O3 exhibits a weak localized state at 0.3 eV above the top of its valence band, possibly due to Zn. 2+ Due to the size mismatch with the oxygen octahedron, its defect state distribution is further away from the conduction band (ΔE≈2.0eV), exhibiting excellent insulation stability (b); at 600℃ and a thickness of 1.5mm, an RLmin value of -49.93dB was obtained (c) and the best EAB at 2.13GHz was achieved (d).
[0048] Example 2
[0049] High-entropy ceramics Ba(Cu) 0.2 Yb 0.2 Ta 0.2 Nb 0.2 V 0.2 O3, where V Cu =+2,V Yb =+3,V Ta =+5,V Nb =+5,V V =+5.
[0050] 1. Satisfies +2≤V Cu ≤+6; +2≤V Yb ≤+6; +2≤V Ta ≤+6; +2≤V Nb ≤+6; +2≤V V ≤+6; V Zn +V Yb +V Ta +V Nb+V V =+20; and includes Yb in rare earth ion doped systems. 3+ V in transition metal ion doped systems 5+ Ta in high bond energy ion doped systems 5+ .
[0051] 2. The calculation yields t = 1.02.
[0052] Its preparation process is as follows:
[0053] Step 1: Mix BaCO3, CuO, Yb2O3, Nb2O5, Ta2O5 and V2O5 powders according to the molar ratio of each metal ion of 10:2:2:2:2:2;
[0054] Step 2: Add an appropriate amount of anhydrous ethanol to the mixed powder, and then ball mill at 300 r / min for 24 h. After the process, transfer the mixture to an oven and dry it at a constant temperature of 60℃.
[0055] Step 3: After grinding the dried powder, sinter it at 1000℃ for 10 hours to prepare precursor powder;
[0056] Step 4: Take an appropriate amount of precursor powder, add PVA to it, with a mass ratio of 1:1.2, stir evenly and grind, then pass through an 80-mesh sieve, a 100-mesh sieve and a 120-mesh sieve in sequence. The particle size distribution of -80 mesh to +100 mesh is recorded as powder A, the particle size distribution of -100 mesh to +120 mesh is recorded as powder B, and the particle size distribution of 120 mesh is recorded as powder C. Then mix equal masses of powder A, powder B and powder C evenly and pour into a mold with a diameter of 50 mm for cold pressing at a pressure of 10 MPa for 1 min.
[0057] Step 5: Transfer the pressed powder green body to a muffle furnace for sintering. First, slowly heat it to 550℃ at a rate of 1℃ per minute, and then increase the temperature to the target sintering temperature of 1300℃ at a rate of 5℃ per minute to obtain high-entropy ceramic Ba(Cu) 0.2 Yb 0.2 Ta 0.2 Nb 0.2 V 0.2 )O3.
[0058] like Figure 2 As shown, Ba(Cu) 0.2 Yb 0.2 Ta 0.2 Nb 0.2 V 0.2 O3 exhibits a significant lattice contraction phenomenon, with the lattice constant changing from the initial... Adjusted to Effectively suppressed multiphase separation (a); Ba(Cu) 0.2 Yb 0.2 Ta 0.2 Nb 0.2 V 0.2 O3 exhibits higher intensity of localized states, similar to Cu. 2+ The oxygen vacancy tendency is directly related to the shallow defect state near the bottom of the conduction band (1.5eV), which can increase the leakage current and improve the polarization characteristics through trap-assisted tunneling (b); at 600℃ and a thickness of 1.53mm, an RLmin value of -46.09dB (c) and the best EAB of 1.99GHz were obtained (d).
[0059] Example 3
[0060] High-entropy ceramics Ba(Cu) 0.2 Yb 0.2 Ta 0.2 Nb 0.2 V 0.2 O3, where V Cu =+2,V Yb =+3,V Ta =+5,V Nb =+5,V V =+5.
[0061] 1. Satisfies +2≤V Cu ≤+6; +2≤V Yb ≤+6; +2≤V Ta ≤+6; +2≤V Nb ≤+6; +2≤V V ≤+6; V Zn +V Yb +V Ta +V Nb +V V =+20; and includes Yb in rare earth ion doped systems. 3+ V in transition metal ion doped systems 5+ Ta in high bond energy ion doped systems 5+ .
[0062] 2. The calculation yields t = 1.02.
[0063] Its preparation process is as follows:
[0064] Step 1: Mix BaCO3, CuO, Yb2O3, Nb2O5, Ta2O5 and V2O5 powders according to the molar ratio of each metal ion of 10:2:2:2:2:2;
[0065] Step 2: Add an appropriate amount of anhydrous ethanol to the mixed powder, and then ball mill at 300 r / min for 24 h. After the process, transfer the mixture to an oven and dry it at a constant temperature of 60℃.
[0066] Step 3: After grinding the dried powder, sinter it at 1000℃ for 10 hours to prepare precursor powder;
[0067] Step 4: Take an appropriate amount of precursor powder, add PVA to it, with a mass ratio of 1:1.2, stir evenly and grind, passing through a 60-mesh sieve, an 80-mesh sieve and a 100-mesh sieve in sequence. The particle size distribution of -60 mesh to +80 mesh is recorded as powder A, the particle size distribution of -80 mesh to +100 mesh is recorded as powder B, and the particle size distribution of 100 mesh is recorded as powder C. Then mix equal masses of powder A, powder B and powder C evenly and pour into a mold with a diameter of 50 mm for cold pressing at a pressure of 10 MPa for 1 min.
[0068] Step 5: Transfer the pressed powder green body to a muffle furnace for sintering. First, slowly heat it to 550℃ at a rate of 1℃ per minute, and then increase the temperature to the target sintering temperature of 1300℃ at a rate of 5℃ per minute to obtain high-entropy ceramic Ba(Cu) 0.2 Yb 0.2 Ta 0.2 Nb 0.2 V 0.2 )O3.
[0069] like Figure 3 As shown, Ba(Cu) 0.2 Yb 0.2 Ta 0.2 Nb 0.2 V 0.2 O3 is a blocky material formed by grain aggregation, with uniform distribution of each metal element (a and b); at 600℃ and a thickness of 2.12 mm, an RLmin value of -54.09 dB (c) and an optimal EAB of 2.81 GHz were obtained (d).
[0070] Comparative Example 1
[0071] Same as Example 1, except that in step (4), the powder is passed through an 80-mesh sieve and then the powder with a particle size distribution of 80 mesh is poured into a mold with a diameter of 50 mm for cold pressing.
[0072] The prepared sample was tested and found to have an RLmin value of -36.09 dB and an optimal EAB of 0.7 GHz at 600 °C and a thickness of 2.12 mm.
[0073] Comparative Example 2
[0074] High-entropy ceramics Ba(Zn) 0.2 Yb0.2 As 0.2 Nb 0.2 V 0.2 O3, where V Zn =+2,V Yb =+3,V As =+5,V Nb =+5,V V =+5.
[0075] 1. Satisfies +2≤V Zn ≤+6; +2≤V Yb ≤+6; +2≤V As ≤+6; +2≤V Nb ≤+6; +2≤V V ≤+6; V Zn +V Yb +V As +V Nb +V V =+20; Only includes Yb in rare earth ion doped systems 3+ V in transition metal ion doped systems 5+ .
[0076] 2. The calculation yields t = 1.05.
[0077] The preparation process is the same as in Example 1.
[0078] like Figure 4 As shown, the prepared sample obtained an RLmin value of -7.14dB at 600℃, indicating no effective absorption bandwidth.
[0079] Comparative Example 3
[0080] High-entropy ceramics Ba(Zn) 0.2 Yb 0.2 Ta 0.2 Nb 0.2 As 0.2 O3, where V Zn =+2,V Yb =+3,V Ta =+5,V Nb =+5,V As =+5.
[0081] 1. Satisfies +2≤V Zn ≤+6; +2≤V Yb ≤+6; +2≤V Ta ≤+6; +2≤V Nb ≤+6; +2≤V As ≤+6; V Zn +VYb +V Ta +V Nb +V As =+20; Only includes Yb in rare earth ion doped systems 3+ Ta in high bond energy ion doped systems 5+ .
[0082] 2. The calculation yields t = 1.04.
[0083] The preparation process is the same as in Example 1.
[0084] like Figure 5 As shown, the prepared sample, after testing, achieved an RLmin value of -21.4 dB and an optimal EAB of 1.239 GHz at 600 °C and a thickness of 1.76 mm.
[0085] Comparative Example 4
[0086] High-entropy ceramics Ba(Zn) 0.2 Cr 0.2 Ta 0.2 Nb 0.2 V 0.2 O3, where V Zn =+2,V Cr =+3,V Ta =+5,V Nb =+5,V V =+5.
[0087] 1. Satisfies +2≤V Zn ≤+6; +2≤V Cr ≤+6; +2≤V Ta ≤+6; +2≤V Nb ≤+6; +2≤V V ≤+6; V Zn + Cr +V Ta +V Nb +V V =+20; V only includes transition metal ion doped systems 5+ Ta in high bond energy ion doped systems 5+ .
[0088] 2. The calculation yields t = 1.04.
[0089] The preparation process is the same as in Example 1.
[0090] like Figure 6As shown, the prepared sample, after testing, achieved an RLmin value of -41.3dB and an optimal EAB of 0.126GHz at 600℃ and a thickness of 3.62mm.
Claims
1. A design method for a high-entropy ceramic microwave absorbing material, characterized in that, Includes the following steps: (1) Determine BaBO3 perovskite as the structural model and combine the five ions at the B site in BaBO3 perovskite in equal proportions; (2) Based on the synergistic polarization of the multi-level system, three ion-doped systems were identified, one of which is a rare-earth ion-doped system, including Yb 3+ Ho 3+ Er 3+ Eu 3+ One type is the transition metal ion doped system, including V 5+ Mn 3+ Fe 2+ Cr 3+ One of them; the third is a high bond energy ion doping system, including Ta 5+ Hf 4+ Zr 4+ Mo 6+ One of them; (3) The five ions at the B site are denoted as V1, V2, V3, V4, and V5, respectively, satisfying +2≤V1≤+6; +2≤V2≤+6; +2≤V3≤+6; +2≤V4≤+6; +2≤V5≤+6; V1+V2+V3+V4+V5=+20; and the five ions at the B site must include the three ion doping systems in step (2); (4) Establish the mapping relationship between the tolerance factor theory and the structural stability of BaBO3 perovskite, and the formula is as follows: Among them, R A R B Ba 2+ The average ionic radius of the five ions at the B site, R O Representing O 2- The ionic radius; (5) Based on the mapping relationship in step (4), calculate the tolerance factor of the element combination that meets the conditions in step (3), and select the element combination with a t interval of 1-1.05, which is determined as the high-entropy ceramic required for design.
2. A method for preparing a high-entropy ceramic microwave absorbing material, characterized in that, Includes the following steps: (1) BaCO3 was mixed with various metal oxide powders and ball-milled, and then sintered at 900-1100℃ to obtain precursor powder; (2) Mix the precursor powder and PVA thoroughly, pass them through several sieves with increasing mesh sizes, and then mix equal masses of powders with different particle size distributions and pour them into a mold for cold pressing to obtain a green body. (3) The green body is sintered at 1200-1400℃ to obtain high-entropy ceramic microwave absorbing material. Further, in step (1), the molar ratio of Ba in BaCO3 to the total amount of metals in each metal oxide is 1:1; the molar ratio of each metal in the metal oxide is 1:1:1:1:
1.
3. The preparation method according to claim 2, characterized in that, In step (2), the mass ratio of the precursor powder to PVA is 1:1 to 1.
5.
4. The preparation method according to claim 2, characterized in that, In step (2), the mesh sizes of the sieves are 60 mesh, 80 mesh and 100 mesh respectively. Particle size distribution of -60 mesh to +80 mesh is denoted as powder A, particle size distribution of -80 mesh to +100 mesh is denoted as powder B, and particle size distribution of 100 mesh is denoted as powder C. Take equal mass of powder A, powder B and powder C and mix them evenly.
5. The preparation method according to claim 2, characterized in that, In step (2), the mesh sizes of the sieves are 80 mesh, 100 mesh and 120 mesh respectively. Particle size distribution of -80 mesh to +100 mesh is denoted as powder A, particle size distribution of -100 mesh to +120 mesh is denoted as powder B, and particle size distribution of 120 mesh is denoted as powder C. Take equal mass of powder A, powder B and powder C and mix them evenly.
6. The preparation method according to claim 2, characterized in that, In step (2), the pressure of the cold pressing is 8-15 MPa and the time is 30-90 s.
7. The preparation method according to claim 2, characterized in that, In step (3), the heating procedure of the sintering process is as follows: first, slowly heat to 550°C at a rate of 1°C / min, and then heat to the target sintering temperature of 1200-1400°C at a rate of 5°C / min.
8. The high-entropy ceramic microwave absorbing material prepared by the preparation method according to any one of claims 2-7.
Citation Information
Patent Citations
Lightweight broadband wave-absorbing material as well as preparation method and application thereof
CN117263165A
Magnetic high-entropy perovskite wave-absorbing material and preparation method thereof
CN118993733A
Surface mechanical alloying coated zinc carbonyl iron powder absorbent and preparation method thereof
CN119609126A